PERLINDUNGAN HUKUM PIHAK KETIGA TERHADAP KEBERATAN ATAS PUTUSAN PENGADILAN DALAM PERKARA KORUPSI - Ibrahim, Muhamad Nur (Katalogis, 2016)
The formulation of the problem of how the legal protection of third parties in the recovery of goods hers were seized under a court decision in a corruption case and how the procedure of filing a legal remedy of appeal a third party against a court decision on confiscation of goods in corruption under the Act, the purpose of the study was to assess the legal protection for third parties in the recovery of her belongings were seized under a court decision in a corruption case and review procedures for filing legal remedy of appeal a third party against a court decision on confiscation of goods in corruption according to the legislation and judicial practice, using the method of normative research with the research shows that a third party is acting in good faith in regain her belongings were seized in the corruption has gained legal protection throughout the third party is able to prove that he is not related to criminal offenses committed by the convict, legal protection for third parties is not optimal, because in fact the judge was inconsistent in applying the provisions of Article 19 law No. 31 of 1999 Jo law No. 20 of 2001 on Corruption Eradication and procedure of filing a legal remedy of appeal pursuant to Article 19 of law No. 31 of 1999 Jo law No. 20 of 2001 on Corruption Eradication still rise to various interpretations due to the vagueness of norms , consequently the court decision in the case of third parties acting in good faith objections tends to vary depending on their interpretation of Judges that do not reflect the justice and legal certainty.